2014
DOI: 10.1177/0093854814554447
|View full text |Cite
|
Sign up to set email alerts
|

Victimization, Offending, and Perceived Risk for Early Violent Death

Abstract: Research indicates that adolescents tend to overestimate their risk for early death, and those who anticipate early deaths are at risk for numerous negative consequences. Little is known, however, about the factors that influence early violent death expectations. The present study develops and tests hypotheses about the influence of victimization and offending on perceived risk for early violent death using longitudinal data collected from a nationally representative sample of American adolescents. Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Yet, considering that victimization is not randomly distributed in the population, and in particular that violent crime is associated with risky routine activities in similar ways as offending (Wilcox and Cullen 2018;Wilcox et al 2014) and often embedded in ongoing interpersonal conflicts (Black 1983), some people may, in fact, have a well-founded sense of imminent victimization risks, a notion that has rarely been investigated in fear of crime research. In an analysis of Add Heath data, Tillyer (2015) found that adolescents who were gang members and involved in violent offending had a strongly increased risk perception of being killed before the age of 21. In discussing this anticipatory effect, Denkers and Winkel (1998) even suggested that "crime does not cause a deterioration of well-being, but rather that individuals who are less satisfied with life are more likely to become a victim of crime".…”
Section: Between-and Within-person Modelingmentioning
confidence: 99%
“…Yet, considering that victimization is not randomly distributed in the population, and in particular that violent crime is associated with risky routine activities in similar ways as offending (Wilcox and Cullen 2018;Wilcox et al 2014) and often embedded in ongoing interpersonal conflicts (Black 1983), some people may, in fact, have a well-founded sense of imminent victimization risks, a notion that has rarely been investigated in fear of crime research. In an analysis of Add Heath data, Tillyer (2015) found that adolescents who were gang members and involved in violent offending had a strongly increased risk perception of being killed before the age of 21. In discussing this anticipatory effect, Denkers and Winkel (1998) even suggested that "crime does not cause a deterioration of well-being, but rather that individuals who are less satisfied with life are more likely to become a victim of crime".…”
Section: Between-and Within-person Modelingmentioning
confidence: 99%